Analysis of the regional efficiency of european funds in Spain from the perspective of renewable energy production: The regional dimension - Mugambi, Paul (2021)
During the 2010–2020 period, the European Union (EU) launched a growth strategy based on three fundamental pillars: smart growth, sustainable growth, and inclusive growth. Aiming to finance the projects related to these growth pillars, the EU used mainly the Rural Development Funds, the Structural Funds, those derived from the R&D Framework Program, the Trans-European Networks, and the European Investment Bank. This research aimed to determine whether the Spanish regions maintain homogeneous efficiency levels by using these resources to improve the levels of environmental quality related to renewable energies. A methodology that is frequently used by researchers in efficiency analyses was chosen, the Data Envelopment Analysis (DEA). The main findings revealed that the efficiency in the use of renewable energies is very uneven among the Spanish regions and these differences are maintained throughout the period analyzed. These results highlighted the need of changes regarding the proposed criteria for allocating European resources to finance the projects presented by each Spanish region.